A systematic review of studies evaluating Australian indigenous community development projects: the extent of community participation, their methodological quality and their outcomes. (December 2015) - Snijder, Mieke; Shakeshaft, Anthony; Wagemakers, Annemarie; Stephens, Anne; Calabria, Bianca
Abstract Background Community development is a health promotion approach identified as having great potential to improve Indigenous health, because of its potential for extensive community participation. There has been no systematic examination of the extent of community participation in community development projects and little analysis of their effectiveness. This systematic review aims to identify the extent of community participation in community development projects implemented in Australian Indigenous communities, critically appraise the qualitative and quantitative methods used in their evaluation, and summarise their outcomes. Methods Ten electronic peer-reviewed databases and two electronic grey literature databases were searched for relevant studies published between 1990 and 2015. The level of community participation and the methodological quality of the qualitative and quantitative components of the studies were assessed against standardised criteria. Results Thirty one evaluation studies of community development projects were identified. Community participation varied between different phases of project development, generally high during project implementation, but low during the evaluation phase. For the majority of studies, methodological quality was low and the methods were poorly described. Although positive qualitative or quantitative outcomes were reported in all studies, only two studies reported statistically significant outcomes. Discussion Partnerships between researchers, community members and service providers have great potential to improve methodological quality and community participation when research skills and community knowledge are integrated to design, implement and evaluate community development projects. Conclusion The methodological quality of studies evaluating Australian Indigenous community development projects is currently too weak to confidently determine the cost-effectiveness of community development projects in improving the health and wellbeing of Indigenous Australians. Higher quality studies evaluating community development projects would strengthen the evidence base.